2022
DOI: 10.3390/s22041608
|View full text |Cite
|
Sign up to set email alerts
|

Method for Data Quality Assessment of Synthetic Industrial Data

Abstract: Sometimes it is difficult, or even impossible, to acquire real data from sensors and machines that must be used in research. Such examples are the modern industrial platforms that frequently are reticent to share data. In such situations, the only option is to work with synthetic data obtained by simulation. Regarding simulated data, a limitation could consist in the fact that the data are not appropriate for research, based on poor quality or limited quantity. In such cases, the design of algorithms that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Each of the methods has advantages and disadvantages, based on this fact no unique method can be chosen in any situation. Methods must be chosen and designed based on considerations like the data specificity and data quantity [26]. Sometimes it is a good approach to make hybridizations of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the methods has advantages and disadvantages, based on this fact no unique method can be chosen in any situation. Methods must be chosen and designed based on considerations like the data specificity and data quantity [26]. Sometimes it is a good approach to make hybridizations of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…In Iantovics’ paper [ 5 ], a method for data quality assessment of synthetic industrial data is presented. Synthetic data are necessary because sometimes it is difficult to obtain real data from sensors or machines and use them in another context.…”
Section: Related Workmentioning
confidence: 99%
“…The literature review has shown that there are some useful components in every presented publication, which are also taken up in this paper. From [ 5 , 6 , 7 ], the idea of an indicator to classify good and bad data is used. In this paper, a quality measure will be introduced to compare the different data sets.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…dependent variable of driving forces for LULC dynamics Classi cation Tablea,b Statistics of the Model Goodness-of-t statistics showed that the study to determine whether the model adequately describes the data(Archer & Lemeshow, 2006).Omnibus Tests of Model Coe cients was used to test the model t(Data, 2022). The model is signi cant and the likelihood ratio chi-square test indicated that the full model is a signi cant improvement in t over a null model, x 2 (23.971), P < 0.001.…”
mentioning
confidence: 99%